PENGARUH ARUS KAS OPERASI TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Fahrul Imam Santoso, Fahrul (LPPM Universitas Nias Raya, 2023)
This study examines the effect of operating cash flow on stock returns in the banking industry listed on the BEI. The population in this study was 43 industries in the banking sub-sector, while the sample was ten industries. The analytical tool in this study uses the SPSS application program. The method in this study uses a quantitative data approach with simple linear regression analysis. The results obtained indicate that the operating cash flow variable affects stock returns